Superolein based intravenous lipid emulsion 20% w/w physicochemical characterization, stability and its effect on liver status - Mohd. Haz Hairul Amran; Mohd. Fairuz Danik; Mohd. Shakrie Palan Abdullah; Mohd. Hanif Zulfakar; Ahmad Fuad Shamsuddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Long chain triglycerides (LCT) from soya oil have been reported to cause hepatic abnormalities among patients receiving parenteral nutrition. A new source for LCT is needed to support current therapy. The aims of this study were to develop a good and stable superolein oil based intravenous lipid emulsion 20% (SoLE), and to determine its effect on liver status of an animal model. The emulsion was prepared using superolein oil and medium chain triglyceride oil (1:1), 1.2 g lecithin and homogenized by high pressure homogenization method. The physical stability study was performed based on real-time, accelerated, force degradation and environmental degradation. Chemical stability was measured based on fatty acids and vitamin E contents, peroxide value and acidity value. As the animal model, three rabbits were administered with 1.5 g/kg SoLE for 5 h and repeated daily for three days. The SoLE was found to have good physicochemical characters: 229.07±1.57 nm of particle size; 0.00% of particle > 5 μm; 342.00±1.00 mOsm/kg of osmolarity; -46.67±4.40 mV of zeta potential; 1.72±0.04 cP of viscosity; 7.83±0.06 of pH; 0.80±0.06 kcal/g calorie; 1.74±0.05 mEqO2/kg of peroxide value; and 0.03±0.01% of acidity value, and excellent physicochemical stabilities for up to six months of storage at various temperatures and conditions. The level of plasma lipid and plasma liver enzymes profiles of the rabbits remained statistically unchanged. This study has successfully developed a stable SoLE 20% and it was found to be safe to the liver of the animal model.